Towards a Policy on Assessment Methodology for Malagasy Students at the Universite Des Mascareignes - Kumar, Betchoo Nirmal (European Scientific Journal, ESJ, 2017)
With an increase in the intake of foreign students to the Université des Mascareignes (UdM), there are arguments on reviewing the assessment system in force in the university. It might be correct to assume that universities have the flexibility of providing various forms of assessments but these have to be tailored to the needs of contemporary students. The research is based on the fact that Malagasy and foreign students coming from the African region have different educational backgrounds that differ from the Mauritian Anglo-Saxon inherited system with formal examinations and a little change in evaluations recently. The fact that foreign students are now an integral part of the university revealed that Malagasy students, taken as a sample of the research, tended to favour the use of French language and appeared to be more versed in practical applications of learning provided by the UdM. This situation puts them in slight confrontation with Mauritian students who are more apt to learn by heart and assimilate English language without much difficulty. In view of this situation, the researcher claims that it might be possible to make assessments more flexible and adaptable to such foreign students while confirming that the essence of formal examinations should be maintained. This approach could be more practical as evaluation suited to the needs and of foreign students at the UdM.